Analisis usaha keramba jaring apung ikannila (oreorchromis niloticus) di desa loa deras kecamatan penyinggahan kabupaten kutai barat - Ariadi, Rizal; Abdusysyahid, said; Oktawati, Nurul Ovia (Jurnal Pembangunan Perikanan dan Agribisnis, 2024)
The purpose of this study was to analyze the business income of tilapia floating net cages in Loa Deras Village and determine the level of business feasibility based on value (Revenue Cost Ratio). This research was conducted in January 2021 – June 2022 in Loa Deras Village, Peninggahan District, West Kutai Regency. The data collection method used is a case study, which is a detailed study of a research subject. The sampling method used is Saturated Sampling or Census with a total of 30 respondents. The data obtained was analyzed using a qualitative-quantitative descriptive method with a focus on income analysis methods and business feasibility based on parameters (Revenue Cost Ratio) of Tilapia floating net cage business in Loa Deras Village. Based on the results of the analysis, the total income value of the respondents was Rp. 239,337,778/month with an average of Rp. 7,977,926/month/respondent. The results of the income analysis show that floating net cage entrepreneurs are profitable and feasible to continue, as evidenced by the ratio of revenues being greater than the costs incurred which can be explained by the average R/C ratio value of 2.3 times greater.